2022
DOI: 10.3389/fphys.2022.949351
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and cardiorespiratory fitness in overweight or obese people post COVID-19: A comparative study

Abstract: The present study aimed to evaluate the body composition and cardiorespiratory fitness of overweight or obese people after COVID-19. 171 volunteers of both sexes (men, n = 93 and women, n = 78) between 19 and 65 years old were allocated into three groups according to the severity of their symptoms of COVID-19: non-hospitalized people/mild symptoms (n = 61), hospitalized (n = 58), and hospitalized in an intensive care unit-ICU (n = 52). Two laboratory visits were carried out 24 h apart. First, a medical consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
20
1
3
Order By: Relevance
“…Lower CRF as a consequence of severe symptoms among middle- to older aged group may be explained that progressive deterioration of protective immune response is accompanied with increasing age, resulting in susceptibility to infection and experiencing more tissue-damaging inflammation ( 42 ). Obesity and physical activity status have additionally been proposed as factors for worsening symptoms ( 21 , 43 ). Among included studies, COVID-19 survivors with advancing age and more severe symptoms were obese ( 23 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower CRF as a consequence of severe symptoms among middle- to older aged group may be explained that progressive deterioration of protective immune response is accompanied with increasing age, resulting in susceptibility to infection and experiencing more tissue-damaging inflammation ( 42 ). Obesity and physical activity status have additionally been proposed as factors for worsening symptoms ( 21 , 43 ). Among included studies, COVID-19 survivors with advancing age and more severe symptoms were obese ( 23 , 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent evidence synthesis has documented that severe symptoms were associated with advancing age ( 20 ). In addition, a very recent study has revealed that the more worsening symptoms, the lower CRF level ( 21 ). As the evidence suggests, it is likely that older age is a driving factor in further reducing CRF.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were recruited via referral from the hospital institution after medical discharge. Data for this broad research project 9 were collected between August and December 2021, performing clinical assessments (blood pressure measurement, blood glucose, oxygen saturation, physical assessment with anthropometry, body composition with electrical bioimpedance, and cardiorespiratory stress test) and applying a standardized questionnaire with 90 open-ended and closed-ended questions, including data on medical history, pre-existing diseases, need for hospitalization, time and type of hospital stay, anosmia, and ageusia (with questions about the presence of symptoms during and/or after COVID-19 and duration of symptoms after hospital discharge).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, people with obesity hospitalized for COVID-19 tend to lose a large proportion of lean mass due to physical inactivity and hospital nutritional therapy, as well as low-grade inflammation [ 18 ]. In addition, there is also a reduction in cardiorespiratory capacity in people with obesity hospitalized for COVID-19 [ 19 , 20 , 21 ]. Considering the above, this systematic review aimed to analyze the available studies that identified overweight and/or obesity as a risk factor for mortality, the use of respiratory support, and changes in biomarkers in adults hospitalized with SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%